Distribution characteristics of microplastics in Zhubi Reef from South China Sea. (December 2019) - Huang, Youjia; Yan, Muting; Xu, Kaihang; Nie, Huayue; Gong, Han; Wang, Jun
Abstract: As a new type of emerging pollutant in the ocean, microplastics have received global attention in recent years. Considering the increasing amount of human activities around the South China Sea, it is important to determine the current status of microplastic pollution in this region. In this study, we analyzed the abundance and distribution of microplastics at Zhubi Reef in the South China Sea. Microplastic abundance ranged from 1400 to 8100 items/m 3 of surface water, which was much higher than the values reported from other ocean areas. About 80% of the microplastics were smaller than 0.5 mm in size. Fibers and pellets comprised the most common microplastic types. The dominant microplastics were transparent or blue in color. The main polymer types were polypropylene (25%) and polyamide (18%). In general, our results revealed Zhubi Reef was contaminated with microplastics, which were likely derived from the intensive fisheries in the area and emissions from coastal cities. This study also provides baseline data that are useful for additional studies of microplastics in the South China Sea. Graphical abstract: Image 1 Highlights: The first report on microplastics pollution in from Nansha Islands. Blue microbeads were the dominant type in surface water from Nanxun Reef. PVC was the major polymer type in surface water from Nanxun Reef. Abstract : Microplastics pollution in South China Sea.